Uji Validitas Konstruk The Modified Mini Mental State-Test (3MS) - Gevi Khairunnisa; Pricillia Putri; Febbealya Cheerson; Fenny Junita; Christiany Suwartono; Magdalena Halim (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2013)
Decline in cognitive function is a clinical manifestation occurs as part of the aging process which is inevitable in elderlies. Decline in cognitive function is often referred to as dementia. One of the measuring devices made to measure cognitive function was MMSE by Folstein, Folstein, and McHugh. As the MMSE had shortcomings such as floor and ceiling effects, also the failure to distinguish between mild and severe dementia, in 1987.Teng and Chui made the Modified Mini Mental State (3ms) which also measured cognitive function. Therefore, this study aims to adapt and create norms in accordance with the conditions in Indonesia and to test the construct validity of 3ms. The data was obtained from 152 elders lived in Jakarta and surrounding areas. The method of analysis used is Confirmatory Factor Analysis (CFA) with the help of software LISREL 8.7. The test results proved that Indonesia 3ms version consists of 3 factors.